“The air in which we moved”: Atmospheres and Media - Polina Yu. Rybina (Литература двух Америк, 2025)
One of the narrators in Henry James’s “The Turn of the Screw”, the governess at Bly Manor, is aware of the weirdness of the situation in general (the ghostly apparitions) as well as her interactions with the children. She feels that strangeness permeates the environment — “the air in which we moved”. The unnamed and the untouched — those elusive phenomena — determine their lives, dominate all conversations and capture their attention. The paper examines the significance of applying the idea of atmosphere to the analysis of James’s prose, as well as its transmedia adaptations (filmic or theatrical). Offering commentary on the concepts of atmosphere and atmospheric effects, I rely upon the works of neo-phenomenologists (Herman Schmitz, Gernot Böhme, Tonino Griffero), performance theorists (Richard Schechner, Erika Fischer-Lichte), and narratologists (Steffen Hven, Rick Warner). The primary focus is on the concept of “atmospheric perception” introduced by Hven to refer to the viewer’s pre-reflexive apprehension of the affective charge of the film narrative. Ideas on atmospheres are relevant in contemporary adaptation studies (Linda Hutcheon, Thomas Leitch). When literary sources migrate to different media (film, theatre, video games), we respond not only to the transformations of themes and plots but the variations of atmospheres and moods (David Richard). The importance of what performance theorist Fischer-Lichte has dubbed “the re-enchantment of the world” — that is, the influence of the many phenomena that defy our volition and knowledge — is revealed when discussing atmospheric effects, whether in literature or film. Exploring atmospheres helps us stay mentally sharp and emotionally fresh while comprehending the limits of our control over the environment.